Evaluation of a rumen modifier to limit pellet intake in beef brood cows - Gleason, Claire B.; Wilson, T. Bain; Mercadante, Vitor R. G.; White, Robin R. (Frontiers in Animal Science, 2022)
Winter supplementation of gestating beef cows is often necessary to ensure energy and protein requirements remain satisfied. However, it is difficult to prevent over- or under-consumption by individual animals fed in a group. The objective of this study was to evaluate the intake limiting effects of 3 levels of tea saponin (TS) on pelleted feed consumption when compared with a TS-free control treatment. Commercial beef cows in late gestation (n = 24) were allocated to 1 of 4 treatments delivered via a pelleted feed supplement: 0% (A), 0.16% (B), 0.32% (C), or 0.64% (D) TS on a dry matter basis. Cows were assigned so that initial mean body weights and body condition scores were similar among treatment groups. Supplement was delivered once daily via Calan gates at a rate of 2.5% of BW for 42 days. Refusals were collected daily to calculate intake. Treatment differences were observed for pellet DMI, cow BW, and cow BCS (P < 0.0001). Cow hay intake, calf birth weight, and calf weaning weight were unaffected by treatment (P > 0.05). Dry matter intake of pellets as a percent of BW (DMIBW) was significantly different for all treatments (P < 0.0001) with intake declining as TS content increased. Considerable variability in DMIBW of all treatments was observed from day 0 to 15 but intakes plateaued between 1.75 and 2.5% DMIBW for the remainder of the trial with Treatment D intake remaining noticeably lower than the other treatments. Treatment D was found to be successful at limiting pellet intake to an average DMIBW of 1.51%. This study concluded that short-term pellet intake can be limited by inclusion of TS, highlighting it as a potential intake limiter product for beef cattle producers.